Działania aparatu bezpieczeństwa wobec Łucjana Jankowskiego (1901-1958) - harcerza i społecznika z Grodziska Wielkopolskiego = The actions of the security apparatus on Łucjan Jankowski (1901-1958) - a scout and social activist from Grodzisk Wielkopolski - Bartkowiak, Przemysław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper introduces a person from Grodzisk, a scout and social activist Łucjan Jankowski who was born in 1901 in Poznań. The text also presents the lot of scouting in Grodzisk in the years 1945-1949. In Grodzisk Wielkopolski, like in the rest of the country, Boy and Girl Scouts paid a high price for their participation in the creation of the Polish Scouting Association (Polish abbr. ZHP) as well as for the activity in ZHP in the second half of the 40s of the twentieth century.
Keywords: czasopismo; czasopismo akademickie; Ziemie Zachodnie; stosunki polsko-niemieckie; pogranicze polsko-niemieckie; historia